Effect of Erbium on Microstructure and Hardness Properties of Aluminium LM30 Alloy - Sulaiman, Siti Noradilah; Ahmad, Rosli (Research Progress in Mechanical and Manufacturing Engineering, 2023)
The development of aluminium alloys aims to improve the material's strength, ductility, thermal stability, and weldability to attain a high degree of overall performance. Aluminium is desirable since it is relatively inexpensive and lightweight. In this study, the experiment will be conducted by using optical microscopy to examine the microstructure and hardness test to determine the mechanical properties. Both testings showed an improvement in the microstructure and hardness value of the aluminium LM30 alloy after the addition of Er with different amounts of composition. Observation by using an optical microscope revealed that the unaltered alloy had a coarse plate-like structure. The best modification influenced the Si phases, which were modified into fine particle and short rods. Vicker’s hardness test was used to study the mechanical properties with varied Er concentrations. The hardness value also revealed that the addition significantly enhanced the hardness properties of the Al LM30 alloy, which was then treated with erbium.